Performance of EPMp broiler ducks feed with various levels of dietary lysine up to 10 weeks of age - Maijon Purba; Arnold P. Sinurat (Indonesian Center for Animal Research and Development (ICARD), 2017)
Determining the optimum level of lysine in the ration will be a significant effort to avoid poor growth in duck husbandry. The purpose of this study was to determine the optimum dietary lysine requirement for EPMp broiler ducks, raised up to 10 weeks of age. The study was designed in a completely randomized design (CRD) with 4 dietary treatments, and 4 replicates. Each replicate consisted of 10 ducks. The 4 treatments were diets, containing lysine: 0.60% (T1); 0.70% (T2); 0.80% (T3) and 0.90% (T4). Variables measured included: feed consumption, body weight gain, feed conversion ratio (FCR), carcass and carcass cuts percentages. The results showed that the performance of 10 weeks of age EPMp broiler duck was significantly affected by the level of dietary lysine (P<0.05). The average body weight gain and the FCR of the duck were significantly affected (P<0.05) by dietary lysine level, but not for feed consumption and percentage of carcass (P>0.05). The average body weight gain of EPMp duck with T4 treatment (0.90% lysine) was significantly higher than that T1 (0.60% lysine) but did not significantly difference (P>0.05) with T2 and T3. The average FCR of EPMp duck under T3 and T4 were significantly (P<0.05) higher than that of EPMp duck under T1. It was concluded that the optimum dietary lysine to produce maximum body weight gain of EPMp duck raised up to 10 weeks of age was 0.70%, while for minimum FCR were at the level of 0.80% and 0.90%.